Public Service Innovation Strategy Towards Smart Government - Wiwit Agustina; Muhammad Fazil; Dany Luqyana Idris; Nur Ayu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze public service innovation strategies in realizing smart government and identify supporting and inhibiting factors in their implementation. Digital transformation in government is an urgent need in the information technology era, especially to improve the efficiency, transparency, and accountability of public services. This study uses a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation studies of government agencies implementing digital-based public service innovations. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and methods. The results show that public service innovation strategies towards smart government include service digitalization, business process simplification, data integration, strengthening transformational leadership, and increasing human resource capacity. The implementation of innovations has been proven to increase service time efficiency, information transparency, and public participation.Â